Experiments on flux qubits with pi-shifters - Feofanov, Alexey (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2011)
The results of the research re-ported in this work show that tunable gap flux qubits have a potential for building quantum registers. Cavities coupled to flux qubits can be used for in-formation storage and transfer between qubits. SFS π-shifters provide a simple approach to bias multi-qubit circuits. A possibility to change the qubit resonance frequency while preserving qubit coherence enables implementation of switchable coupling between qubits and cavities.